Biochemical and Functional Characterization of a Metalloprotease from the Thermophilic Fungus Thermoascus aurantiacus - Merheb-Dini, Carolina [UNESP]; Cabral, Hamilton [UNESP]; Leite, Rodrigo S. R. [UNESP]; Zanphorlin, Leticia M. [UNESP]; Okamoto, Debora N. [UNESP]; Bonilla-Rodriguez, Gustavo Orlando [UNESP]; Juliano, Luiz; Arantes, Eliane C.; Gomes, Eleni [UNESP]; da Silva, Roberto [UNESP] (Amer Chemical Soc, 2009)
Protease production was carried out in solid state fermentation. The enzyme was purified through precipitation with ethanol at 72% followed by chromatographies in columns of Sephadex G75 and Sephacryl S100. It was purified 80-fold and exhibited recovery of total activity of 0.4%. SDS-PAGE analysis indicated an estimated molecular mass of 24.5 kDa and the N-terminal sequence of the first 22 residues was APYSGYQCSMQLCLTCALMNCA. Purified protease was only inhibited by EDTA (96.7%) and stimulated by Fe(2+) revealing to be a metalloprotease activated by iron. Optimum pH was 5.5, optimum temperature was 75 degrees C, and it was thermostable at 65 degrees C for 1 h maintaining more than 70% of original activity. Through enzyme kinetic studies, protease better hydrolyzed casein than azocasein. The screening of fluorescence resonance energy transfer (FRET) peptide series derived from Abz-KLXSSKQ-EDDnp revealed that the enzyme exhibited preference for Arg in P(1) (k(cat)/K(m) = 30.1 mM(-1) s(-1)).
Keywords: Thermoascus aurantiacus; Solid state fermentation (SSF); metalloprotease; Thermostability; fluorescent peptides; N-terminal sequence